Challenges and Problems of Teaching English for Adult Learners: A Case Study of Teaching English Using an Online Platform - Alvin Taufik; Nurdiana Nurdiana (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The pandemic is not over yet; Therefore, teaching and learning English with an online platform is still preferable. Like any other medium of instruction, an online platform has its challenges and problems, particularly in teaching English to lower-level adult learners. Shumin (1997) has mentioned several factors influencing the development of adult learners’ speaking abilities. They are age, sociocultural factors, emotions, self-esteem, empathy, anxiety, attitude, and motivation. In relation to online learning, Altakhaineh, Alhendi, Dweikat (2021) state that the problems faced by students and educators are similar. They are time management, teaching methods, lack of encouragement and motivation, and lack of knowledge regarding online teaching tools. This research, therefore, aims to investigate the specific challenges and problems of teaching English to lower-level students through Zoom in the Indonesian context. This research is unique because the class is participated by people from three areas in Indonesia. Since they come from different areas, the facilities and access that they have and can make use of will vary. The research will start with a pre-test. Then, the teaching/research will start from late October 2022 to early February 2023. The result of this research is to identify the specific challenges and problems of online teaching English to low-level adult learners and the method/s used/can be used to overcome them. Keywords: Challenge, Problems, Online teaching and learning, low-level, adult learners